Certifying Gender Equality in Research: Lessons Learnt From Athena SWAN and Total E-Quality Award Schemes - Tzanakou, Charikleia; Clayton-Hathway, Kate; Humbert, Anne Laure (Frontiers in Sociology, 2021)
In the past two decades, many Certification and Award schemes (CAs) related to gender equality, diversity and inclusion have emerged in the higher education, research and industry sectors. According to a recent report, there are as many as 113 CAs which have been identified across Europe and beyond. These CAs aim at addressing inequalities in relation to the grounds of sex, gender, race, sexual orientation, disability, among others. The high number of CAs, and their continued growth, has taken place in parallel to the shift of policies and efforts from ‘fixing individuals’ to ‘fixing the system’. In these schemes, gender equality is often understood as a structural, systemic challenge, with a recognition that advancing gender equality is complex and requires drivers and interventions at micro, meso and macro level. Studies focused on analysing and evaluating gender equality initiatives in higher education have been scarce, and often limited to specific schemes. This paper aims to fill this gap by providing a better understanding of the CAs landscape through comparing two of the main gender equality schemes used by research-performing organisations in Europe Athena SWAN (in the UK) and Total E-quality Award (in Germany). Based on qualitative interviews with stakeholders across Europe and document analysis, this paper focuses on strengths, challenges faced by and the impact of these CAs. This comparative exercise highlights particular learning points that can inform potential reviews of existing schemes and/or the development of new schemes such as a Europe-wide scheme. The latter is the focus of a Horizon 2020 project entitled CASPER (Certification-Award Systems to Promote Gender Equality in Research), which aims at making recommendations to the European Commission as to the feasibility of a Europe-wide CAs for gender equality in research organisations.